Structural characteristics of strategic efficiency of the aviation industry projects - A. V. Bondarenko (Вестник университета)
The factors that constrain the competitiveness of domestic products of the aviation industry in the global market have been reflected. The author’s interpretation of the concept «strategic efficiency of the project» has been introduced. In addition to the commercial efficiency of systemically important projects of the aviation industry, the additional effects of their implementation have been presented schematically, clearly reflecting the attractiveness of these projects for investors and the state. The essence of the structural characteristics of the strategic effectiveness of the project has been highlighted, and the indicators, by which they can be evaluated using the standard rating method, have been enumerated.